2023
DOI: 10.1186/s12885-023-10584-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel cuproptosis-related long non-coding RNA signature to predict prognosis in prostate carcinoma

Abstract: Background Cuproptosis, an emerging form of programmed cell death, has recently been identified. However, the association between cuproptosis-related long non-coding RNA (lncRNA) signature and the prognosis in prostate carcinoma remains elusive. This study aims to develop the novel cuproptosis-related lncRNA signature in prostate cancer and explore its latent molecular function. Methods RNA-seq data and clinical information were downloaded from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, in PCa, studies related to cuproptosis are still in the preliminary stage and most of them have focused on cuproptosis-related long non-coding RNA (lncRNA). Several studies have now reported that cuproptosis-related lncRNA have a better prognostic role in predicting PCa ( 43 , 44 ). However, studies on cuproptosis-related coding genes in PCa are rarely reported, and the role of cuproptosis in PCa remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, in PCa, studies related to cuproptosis are still in the preliminary stage and most of them have focused on cuproptosis-related long non-coding RNA (lncRNA). Several studies have now reported that cuproptosis-related lncRNA have a better prognostic role in predicting PCa ( 43 , 44 ). However, studies on cuproptosis-related coding genes in PCa are rarely reported, and the role of cuproptosis in PCa remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmarks of this tumor were characterized by uncontrolled cell proliferation [ 24 , 25 ], making the establishment of prognostic models based on molecular markers of programmed cell death and physiological process a hot topic in current risk model explorations. For example, predicting models based on crucial regulatory molecules of cuproptosis [ 26 ], steroid hormone biosynthesis [ 27 ], and m6A methylation [ 28 ] are well established, and their correlation with immune cell infiltration can also be analyzed. Disulfidptosis is a newly discovered form of programmed cell death, which is characterized by the inhibition of intracellular disulfide reductants and the significant enhancement of cell death caused by SLC7A11 under glucose starvation conditions, in contrast to the significant increase in cell death induced by thiol oxidation reagents such as diamide [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, in glioma, FDX1 expression levels were upregulated compared with normal tissues. FDX1 knockdown notably hindered aerobic glycolysis and glioma cell proliferation [134]. Li et al further highlighted that the FDX1 expression is promoted by the c-Myc-YTHDF1 signaling pathway in glioma cells and demonstrated that the c-Myc-YTHDF1/FDX1 axis inhibited the mitophagy and promoted the malignant phenotype of glioma cells [161].…”
Section: Fdx1mentioning
confidence: 99%